Analisis Hukum atas Sistem Pembayaran Uang Kompensasi bagi Pekerja Perjanjian Kerja Waktu Tertentu (PKWT) Kasus Tenaga Security - Destiana, Suhendri Zikri; Suhartini, Endeh; Sihotang, Sudiman; Erbiana, Nyi Mas Gianti Bingah (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study legally analyzes the compensation payment system for workers with a fixed-term employment agreement (PKWT), especially in the case of security personnel. This study discusses the Legal Rules Concerning the Compensation Payment System for Termination of PKWT Workers by the User Company and the Legal Protection Given to Security Personnel as PKWT Workers. The research method used by the author uses a juridical-normative method which aims to analyze the legal loopholes and practices that occur in the implementation of the compensation system. The results of this study are that First, PKWT without a written agreement makes security personnel not get definite protection if the user company does not want to use them. Second, the work agreement between security personnel and the user company can be a basis for protecting the rights and obligations of workers.